The Peculiarities of Forming Life Competencies in the Educational Process in Elementary School - Shevchuk, Krystyna (Pedagogical Discourse, 2015)
The attention is focused on the fact that the changes taking place in modern society require reorienting of the school system for the formation of pupilsʼ life competencies that will enable them to be oriented in todayʼs society, information space, the job market, studies, perform important social tasks, respond to the needs of the time. The concept of «competence» has been spread in connection with the modernization of the education system in Ukraine. It was found that the ability and skills of primary school children, formed in the educational process, mean willingness to reach the goal in training activities, that is to receive «knowledge in action». Based on the analysis of the literature sources it has been determined that the competences of primary school children are formed in the knowledge, experience, values, aptitudes, acquired through training oriented to independent studentsʼ inclusion in the educational process. The acquisition of general learning and target competencies are the foundation of further successful pupilsʼ learning in the secondary school. The concept of «competence» has been specified, which is defined as the ability to apply their knowledge, skills, ways of activity, their own experience in unconventional situations to address specific vital issues. Competence is a personal form, which manifests itself in the active independent human actions. The features of the formation of competencies of primary school pupils through the prism of person-oriented learning, the concepts of activity character of getting education have been analyzed.